2018
DOI: 10.14313/jamris_2-2018/9
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized PID Control by Using GA Optimization Applied to a Quadrotor

Abstract: Quadrotors represent an effective class of aerial robots because of their abilities to work in small areas. We suggested in this research paper to develop an algorithm to control a quadrotor, which is a nonlinear MIMO system and strongly coupled, by a linear control technique (PID), while the parameters are tuned by the Genetic Algorithm (GA). The suggested technique allows a decentralized control by decoupling the linked interactions to effect angles on both altitude and translation position. Moreover, the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Thus, obtaining the mathematical model is considered a difficult task [15], [26]- [28]. In this section, the detailed mathematical model of a quadcopter system was derived based on the work done in [29], [30].…”
Section: Quadcopter Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, obtaining the mathematical model is considered a difficult task [15], [26]- [28]. In this section, the detailed mathematical model of a quadcopter system was derived based on the work done in [29], [30].…”
Section: Quadcopter Modelingmentioning
confidence: 99%
“…Therefore, by substitution into equation ( 23), the rotational equations of motion are given by [29]:…”
Section: ω = [̇̇] and ̇= [̈̈]mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the dynamics of unmanned aerial vehicles, including a quadcopter, indicated that external disturbance acting on them led to significant errors in the tracking, laser illumination and homing onto both a moving and stationary target [3,4]. In particular, the control system onboard the aforementioned aerial vehicles, did not provide sufficient resistance to vibrations [5][6][7]. A head with controlled gyroscope (its drive) parameters selected optimally for homing precision, should be chosen in order to minimize the aforementioned error.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the high precision in maintaining the T-LOS in a given position, an optimal controller was designed for the GH. For this reason, despite many control methods used for the unmanned aerial vehicle, known in the literature [9][10][11] a simple PID controller was used to control the flight of the QCUAV, since the drone movement in space does not have to be precisely determined [12][13][14][15][16]. Simplified operation diagram of the system of detection, tracking and laser pointing of a target from the QCUAV deck is shown in Figure 1.…”
mentioning
confidence: 99%